COVID-19 vaccine effectiveness among healthcare workers - Gaio, Vânia (2023)
Publisher Copyright: © Author(s) (or their employer(s)) 2023. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.